The Syntax Analysis In Relative Clause Found In The Novel “The Wonderful Wizard of Oz” - I Made Juliarta (University of Darussalam Gontor, 2022)
The paper analyzed syntax in relative clauses found in the novel “The Wonderful Wizard of Oz”. This research aims to analyze the syntax structure in the relative clause and find out the types of relative clauses found in the novel entitled “The Wonderful Wizard of Oz”. This is library research with qualitative method. The data source of this study was “The Wonderful Wizard of Oz”, a literary work of kid story by Lyman Frank Baum. The theory of relative clauses that was proposed by Quirk (1985) and Sneddon (1996) was used to conduct the data. Furthermore, the researcher used the theory proposed by Brown and Miller to analyze the syntax structure. The data were taken from the novel entitled “The Wonderful Wizard of Oz”. The type of relative clause found is restrictive relative clause with the relative pronoun who.